(untitled) (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2024)
In the judgment we are commenting on, the Second Chamber of the Constitutional Court upholds the appeal filed against the judgment of the Civil Chamber of the Supreme Court of December 23, 2021 by a woman who had been denied the possibility of joining a brotherhood because the incorporation of women was not provided for in its statutes. The Constitutional Court considers that the Supreme Court’s decision is contrary to the right to non-discrimination based on gender, article fourteen of the Constitution, and to the right of association, article 22 of the Constitution, considering that the prohibition is not due to any religious or moral reason and that, although a private association can freely choose the requirements of its members, this power cannot imply discrimination based on sex if the association holds a dominant position in the economic, cultural, social or professional field, which would lead to a breakdown of women in these areas.